The Effect of Work Motivation on Teacherâs Work Performance in Pekanbaru Senior High Schools, Riau Province, Indonesia - Mustafa, M. Nur; Othman, Norasmah (ASPENSI in Bandung, Indonesia, 2010)
ABSTRACT: This study was aimed to examine the perceptions of Pekanbaru State Senior High School teachers, Riau Province, Indonesia about the effect of work motivation on teacherâs work performance. This study used a mixed-model approach as stated by D. Timpe (1998) and P.A. Sahertian (2000). A questionnaire was used in this study. Descriptive analysis and inference based on Statistical Package Social Sains (SPSS-11.5) were used to analyze the data. The findings of the study showed that the level of teacherâs work motivation is medium high with the Mean = 3.390 and SD = 0.483. Whereas, teacherâs work performance is at the medium low level with the Mean = 3.008 and SD = 0.681. T-testing of motivation aspect based on gender was significant. Correlation analysis showed that there was a significant correlation between work motivation and teacherâs work performance. Regression analysis showed that work motivation contributes 61% to teacherâs work performance and this showed that work motivation factor had significant contribution on teacherâs work performance. The implication of this study found that such factor is essential to improve teacherâs performance in Pekanbaru, Riau, Indonesia. However, there are other effects that might have significant effect on teacherâs work performance.Key words: Work motivation, work performance, and State Senior High School teachers in Pekanbaru City, Riau Province.Â Â About the Authors: M. Nur Mustafa is a Lecturer at the Faculty of Teaching and Education Science UNRI (University of Riau) in Pekanbaru City, Riau Province, Indonesia, with his e-mail is: em_nur1388@yahoo.com; and Norasmah Othman is a Lecturer at the Faculty of Education UKM (National University of Malaysia), Bangi, Selangor Darul Ehsan, Malaysia, with her e-mail is: lin@ukm.myHow to cite this article? Mustafa, M. Nur & Norasmah Othman. (2010). âThe Effect of Work Motivation on Teacherâs Work Performance in Pekanbaru Senior High Schools, Riau Province, Indonesiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.3, No.2 [November], pp.259-272. Bandung, Indonesia: Minda Masagi Press, UNIPA Surabaya, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (September 19, 2010); Revised (October 21, 2010); and Published (November 20, 2010). Â Â